PHYSICO-CHEMICAL PROPERTIES OF BIOACTIVE COATED IMPLANTS AND THEIR INTERACTION WITH THE SURROUNDING TISSUES OF THE PREIMPLANT MEDIUM. (LITERATURE REVIEW) (European Journal of Interdisciplinary Research and Development, 2022)
This review is devoted to the analysis of the current understanding of the influence of the physico-chemical properties of implants on the surrounding tissues. The review of modern materials, metals and their alloys, as well as their oxides used for implantation and prosthetics is presented, their biological, physico-chemical, medical and technical properties are analyzed. The works of scientists on the criteria for choosing the implant heads in contact with the epithelium of the gingival cuff, as well as on the biocompatibility of the implant with the tissues of the oral cavity are considered. Possible complications arising from the introduction of implantable materials into the body are indicated, as well as the dependence of the course